Human immunodeficiency virus and acquired immunodeficiency syndrome: correlation but not causation. - Duesberg, P H (1989)
AIDS is an acquired immunodeficiency syndrome defined by a severe depletion of T cells and over 20 conventional degenerative and neoplastic diseases. In the U.S. and Europe, AIDS correlates to 95% with risk factors, such as about 8 years of promiscuous male homosexuality, intravenous drug use, or hemophilia. Since AIDS also correlates with antibody to a retrovirus, confirmed in about 40% of American cases, it has been hypothesized that this virus causes AIDS by killing T cells. Consequently, the virus was termed human immunodeficiency virus (HIV), and antibody to HIV became part of the definition of AIDS. The hypothesis that HIV causes AIDS is examined in terms of Koch's postulates and epidemiological, biochemical, genetic, and evolutionary conditions of viral pathology. HIV does not fulfill Koch's postulates: (i) free virus is not detectable in most cases of AIDS; (ii) virus can only be isolated by reactivating virus in vitro from a few latently infected lymphocytes among millions of uninfected ones; (iii) pure HIV does not cause AIDS upon experimental infection of chimpanzees or accidental infection of healthy humans. Further, HIV violates classical conditions of viral pathology. (i) Epidemiological surveys indicate that the annual incidence of AIDS among antibody-positive persons varies from nearly 0 to over 10%, depending critically on nonviral risk factors. (ii) HIV is expressed in less than or equal to 1 of every 10(4) T cells it supposedly kills in AIDS, whereas about 5% of all T cells are regenerated during the 2 days it takes the virus to infect a cell. (iii) If HIV were the cause of AIDS, it would be the first virus to cause a disease only after the onset of antiviral immunity, as detected by a positive "AIDS test." (iv) AIDS follows the onset of antiviral immunity only after long and unpredictable asymptomatic intervals averaging 8 years, although HIV replicates within 1 to 2 days and induces immunity within 1 to 2 months. (v) HIV supposedly causes AIDS by killing T cells, although retroviruses can only replicate in viable cells. In fact, infected T cells grown in culture continue to divide. (vi) HIV is isogenic with all other retroviruses and does not express a late, AIDS-specific gene. (vii) If HIV were to cause AIDS, it would have a paradoxical, country-specific pathology, causing over 90% Pneumocystis pneumonia and Kaposi sarcoma in the U.S. but over 90% slim disease, fever, and diarrhea in Africa.(viii) It is highly improbable that within the last few years two viruses (HIV-1 and HIV-2) that are only 40% sequence-related would have evolved that could both cause the newly defined syndrome AIDS. Also, viruses are improbable that kill their only natural host with efficiencies of 50-100%, as is claimed for HIVs. It is concluded that HIV is not sufficient for AIDS and that it may not even be necessary for AIDS because its activity is just as low in symptomatic carriers as in asymptomatic carriers. The correlation between antibody to HIV and AIDS does not prove causation, because otherwise indistinguishable diseases are now set apart only on the basis of this antibody. I propose that AIDS is not a contagious syndrome caused by one conventional virus or microbe. No such virus or microbe would require almost a decade to cause primary disease, nor could it cause the diverse collection of AIDS diseases. Neither would its host range be as selective as that of AIDS, nor could it survive if it were as inefficiently transmitted as AIDS. Since AIDS is defined by new combinations of conventional diseases, it may be caused by new combinations of conventional pathogens, including acute viral or microbial infections and chronic drug use and malnutrition. The long and unpredictable intervals between infection with HIV and AIDS would then reflect the thresholds for these pathogenic factors to cause AIDS diseases, instead of an unlikely mechanism of HIV pathogenesis.